Health Inspectors on Local Boards of Health: the Impact on Communities' Environmental Health Governance - Jeff Jones; Asli Aslan; Ginger Fenton (Georgia Southern University, 2019)
Background: This study examines whether having a required health inspector on a local board of health (LBOH) improves the board's information on environmental health. Methods: Analysis uses the national random sample of 351 U.S. LBOHs in the 2011 Profiles collected by the National Association of Local Boards of Health (NALBOH) and examines whether having a required health inspector on a LBOH increases the likelihood it receives information on 10 environmental health topics. Results: LBOHs overall received little information on environmental health, and 48% reported wanting no or little additional information. Having a required health inspector on a LBOH did not increase the likelihood of a LBOH receiving information on 8 environmental health topics. On two additional topics, food safety and groundwater protection, LBOHs with a required health inspector are less likely to report receiving information. A required health inspector board member also did not significantly influence the openness of a LBOH to receiving more information on environmental health. Conclusions: While LBOHs are the predominant public health department governing agencies in the United States, this study points to a low level of training and knowledge about environmental health issues. Having a required health inspector board member also does not improve LBOHs' reported likelihood of receiving information. Keywords: Local boards of health, sanitarians, environmental health, governance, health inspectors